Respiratory therapy for removing bronchial secretions in mechanically ventilated adult patients - Quintana, Adriana Ribeiro Gonçalves (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To compare the effectiveness and safety of respiratory therapy used routinely by physiotherapists to remove bronchial secretions and improve ventilation and health outcomes of mechanically ventilated adult patients. To determine which techniques within respiratory therapy have scientific evidence of efficacy and safety.